1989
DOI: 10.1002/hrm.3930280403
|View full text |Cite
|
Sign up to set email alerts
|

The human resource potential of Americans over 50

Abstract: This article analyzes whether many Americans over age 50 want to return to work. It estimates that among males ages 55 to 64 and females ages 50 to 59 currently not working 1.1 million persons are ready and able to work, have substantial skills and education, would work in high demand occupations, and are flexible about conditions of employment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…One need not fall within an age group to hold a belief about what is important at that time in ones life. The decision to ask how important the issues were for people other than oneself is consistent with the notion of age norms and with previous research on the topic (Byrd & Breuss, 1992;Lawrence, 1988;Neugarten et al, 1965).…”
Section: Normative Aging Beliefssupporting
confidence: 65%
See 3 more Smart Citations
“…One need not fall within an age group to hold a belief about what is important at that time in ones life. The decision to ask how important the issues were for people other than oneself is consistent with the notion of age norms and with previous research on the topic (Byrd & Breuss, 1992;Lawrence, 1988;Neugarten et al, 1965).…”
Section: Normative Aging Beliefssupporting
confidence: 65%
“…Of course, this is a risk anytime one asks about beliefs related to age. Asking about the age at which something is appropriate (i.e., Neugarten et al, 1965) also demands that one respond in terms of age.…”
Section: Beliefs and Career Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Survey evidence suggests that many older Americans would like to work more than they do. McNaught, Barth, and Henderson (1989) analyzed the responses of the retirees in a 1989 Harris poll of 3,500 older Americans. Between 14 and 25 percent of the retirees, representing 1 to 2 million people, reported that they preferred to be working and that they would be able to work if a suitable job were available.…”
Section: Direct Job Creation Training Programs and Anti-discriminatmentioning
confidence: 99%